pharmaceutical-sciences 2020
DOI: 10.36468/pharmaceutical-sciences.655
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Water Molecule-dependent Docking Strategy and Atom-Based 3D QSAR Studies to Design Heat Shock Protein 90 Inhibitors

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…At present, RNAi-based gene therapy in experimental research is on genetic diseases. Research findings from both clinical and experimental studies have indicated that ANFH is attributed to pathophysiological changes due to the accumulation of fat in the bone marrow and abnormal fat metabolism [22,23]. In vitro experiments have confirmed that ethanol can upregulate the expression of PPARc mRNA in BMSCs and accelerate the differentiation of BMSCs into adipocytes, which ultimately leads to the proliferation and accumulation of a large number of adipocytes.…”
Section: Comparison Of Adipogenic Gene Transcription Levels Between Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, RNAi-based gene therapy in experimental research is on genetic diseases. Research findings from both clinical and experimental studies have indicated that ANFH is attributed to pathophysiological changes due to the accumulation of fat in the bone marrow and abnormal fat metabolism [22,23]. In vitro experiments have confirmed that ethanol can upregulate the expression of PPARc mRNA in BMSCs and accelerate the differentiation of BMSCs into adipocytes, which ultimately leads to the proliferation and accumulation of a large number of adipocytes.…”
Section: Comparison Of Adipogenic Gene Transcription Levels Between Groupsmentioning
confidence: 99%
“…In vitro experiments have confirmed that ethanol can upregulate the expression of PPARc mRNA in BMSCs and accelerate the differentiation of BMSCs into adipocytes, which ultimately leads to the proliferation and accumulation of a large number of adipocytes. e bone cells in the femoral head could die due to lipid deposition and fatty degeneration [23,24]. Studies have reported that PPARc may be an important target gene that causes ANFH, and by blocking its expression, ethanol-induced adipocyte differentiation of BMSCs could be aberrated, and preventing the formation of ethanolic ANFH has significant application prospects [25][26][27].…”
Section: Comparison Of Adipogenic Gene Transcription Levels Between Groupsmentioning
confidence: 99%